Pengaruh Media Leaflet terhadap Peningkatan Pengetahuan Wanita Usia Subur dalam Pemilihan Kontrasepsi IUD - Iin Istiqomah; Giat Purwoatmodjo; Tanjung Anitasari Indah Kusumaningrum (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2022)
Background: Users contraception IUD Still more low compared contraception lay Included hearts non LTM. Low use IUD contraception is caused by different factors, praying only is the low level of knowledge. Interest research and testing singer is developing a leaflet as a medium that health promotion efforts to improve knowledge about hearts Intra Uterine Device (IUD) contraceptive at woman of fertile age Sawit subdistrict Tegalrejo In Boyolali. Method: The experimental research study design using design of experiments with the Quasi Experimental Design approach with a pretest-posttest control group. The population research is a women in fertile age aged 20-49 amounted to 495 people. Sampling technique purposive sampling. The number of research samples 35 samples for the the treatment group and 35 samples for the control group. Research instruments used questionnaire. Statistical analysis using t test. Result: The results showed: (1) There is no significant difference in the level of knowledge women in fertile age about IUD contraceptive before and after administration of health education in the control group (p = 0.058 >0.05). (2) There is a significant difference in the level of knowledge women in fertile age about the IUD contraceptive after WUS provided education in the treatment group (p = 0.000<0.05).